1962
DOI: 10.1103/physrev.128.1634
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Dependence of Thermodynamic Properties of Antiferromagnets; Adiabatic Magnetization

Abstract: The thermodynamic properties of cubic or uniaxial antiferromagnets are examined using spin wave theory. The specific heat, magnetization, and parallel susceptibility are shown to be exponentially increasing functions of applied field for values of H Q less than the critical spin-flopping field. Since this field dependence suggests that an antiferromagnet can be cooled by the adiabatic application of a magnetic field, the theory of adiabatic magnetization is investigated. Field-dependent nuclear spin effects ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Equation (6) is equivalent to Eq. (25) of Joenk 22 and, moreover, does reproduce our earlier reported zero-field limit. 23 The magnetic entropy in this range of field and temperature is given as…”
Section: ͑5͒supporting
confidence: 88%
“…Equation (6) is equivalent to Eq. (25) of Joenk 22 and, moreover, does reproduce our earlier reported zero-field limit. 23 The magnetic entropy in this range of field and temperature is given as…”
Section: ͑5͒supporting
confidence: 88%
“…5 It has been known for a long time that the isothermal reduction of a magnetic field gives rise to a decrease in entropy in some antiferromagnetic and ferrimagnetic systems. 6,7 This inverse magnetocaloric phenomenon was supposed to produce small effects and has been largely ignored. Recently, however, it has been shown that in some ferromagnetic 8 and metamagnetic 9 systems, inverse MCE can have an amplitude comparable to the conventional effect detected in giant magnetocaloric intermetallic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the desired temperature for maximum magnetocaloric values are obtained by different stoichiometric sample composition or by sample doping, in order to shift the magnetic transition temperature. Up to now, the literature has not explored systems where antiferromagnetic [10] and ferromagnetic phases coexistence [11] are involved, as well as the behavior of MCE when metamagnetic transitions occurs. For this reason, there is no satisfactory explanation for the behavior observed for DS mag ; which turns to be positive or negative in a given temperature range [12].…”
Section: Introductionmentioning
confidence: 99%